2004
DOI: 10.1097/00130404-200407000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Computerized Tomography Functional Imaging of Esophageal and Colorectal Cancer

Abstract: Positron Emission Tomography/Computerized Emission Tomography (PET/CT) creates fusion images which are a combination of tissue function (PET) and anatomy (CT). PET/CT imaging for esophageal and colorectal cancers improves staging, detection of recurrence, and treatment monitoring. Both tumor types are highly metabolically active in the untreated state, and the glucose analog, 2-[18F]-2-fluoro-2-deoxy-D-glcuose, (FDG), is widely useful as a PET imaging tracer for these malignancies. For esophageal and colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[77][78][79] More recently, PET has been combined with CT (PET/CT) in the same gantry, providing the advantage of anatomic localization of the PET scan abnormalities. [80][81][82][83][84] Yeung et al 85 has reported that combined PET/CT results in increased reader confidence and 53% fewer equivocal readings on the part of the radiologist, as well as an improved positive predictive value compared with PET alone. Currently, there is a general consensus that PET/CT is the most accurate method for staging advanced colorectal cancer, particularly when metastasectomy is being considered and when the patient has possible locoregional recurrent disease.…”
Section: Imagingmentioning
confidence: 99%
“…[77][78][79] More recently, PET has been combined with CT (PET/CT) in the same gantry, providing the advantage of anatomic localization of the PET scan abnormalities. [80][81][82][83][84] Yeung et al 85 has reported that combined PET/CT results in increased reader confidence and 53% fewer equivocal readings on the part of the radiologist, as well as an improved positive predictive value compared with PET alone. Currently, there is a general consensus that PET/CT is the most accurate method for staging advanced colorectal cancer, particularly when metastasectomy is being considered and when the patient has possible locoregional recurrent disease.…”
Section: Imagingmentioning
confidence: 99%
“…Other methods than CT can add to the armamentarium of methods allowing tumor volume detection and assessment of changes therein. PET-CT imaging with 18 FDG has recently been shown to offer advantages in monitoring the response to neoadjuvant treatment of esophageal cancer by measuring the metabolic/volume activity [21, 30, 31]. However, uncertainties regarding which thresholds of standardized uptake value (SUV) during the delineation of tumor remain as a source of variability in previous studies and there is currently no standardized protocol in use.…”
Section: Discussionmentioning
confidence: 99%
“…A solution to the limited spatial resolution of PET comes with its hybridization with CT in a single unit, which allows precise image fusion of the anatomic and functional data improving the interpretation accuracy in oncologic patients [68]. Initial data on esophageal cancer with hybrid PET/CT are limited, but have shown a significant reduction in uncertainty of image interpretation which improves the distinction between benign and malignant causes for FDG-PET positive sites [69].…”
Section: Distant Stage (M-stage)mentioning
confidence: 99%
“…Worldwide, CT scanning of the neck, chest, abdomen, and pelvis remains the single most frequently used study for the evaluation and follow-up of esophageal cancer. Newer modalities such as PET and hybrid PET-CT have added to the pre-eminent role of endoscopic ultrasound (EUS) [3][4][5][6]. MRI currently plays a lesser role, but recent developments in lymph node contrast agents and combination with endoscopic techniques may enhance its distinctive capabilities.…”
Section: Introductionmentioning
confidence: 99%